Respuesta :

Answer:

I love algebra anyways

The ans is in the picture with the  steps how i got it

(hope this helps can i plz have brainlist :D hehe)

Step-by-step explanation:

Ver imagen malmasri25
Ver imagen malmasri25

Answer:

x = - 3, y = - 11

Step-by-step explanation:

Given the 2 equations

y = 7x + 10 → (1)

y = - 4x - 23 → (2)

Substitute y = 7x + 10 into (2)

7x + 10 = - 4x - 23 ( add 4x to both sides )

11x + 10 = - 23 ( subtract 10 from both sides )

11x = - 33 ( divide both sides by 11 )

x = - 3

Substitute x = - 3 into either of the 2 equations and evaluate for y

Substituting into (1)

y = 7(- 3) + 10 = - 21 + 10 = - 11

ACCESS MORE